The Anxious Generation: Why Student Wellbeing is the New Core Curriculum - Amiri, Sayed Mahbub Hasan (International Journal of Geography, Social, and Multicultural Education, 2026)
A profound shift is occurring in educational paradigms, moving beyond a narrow focus on academic achievement to embrace student wellbeing as a fundamental component of school success. Dubbed "The Anxious Generation," today's students face unprecedented levels of stress, anxiety, and burnout, exacerbated by academic pressure, social media, and a post-pandemic world. This article argues that student wellbeing must be reconceptualized as the new core curriculum, asserting that cognitive growth is inextricably linked to social-emotional health. We contend that schools are uniquely positioned to be proactive hubs for mental health support, not merely reactive institutions to academic failure. By integrating Social-Emotional Learning (SEL) principles, mindfulness practices, and restorative disciplines into the fabric of the school day, educators can cultivate resilient, engaged, and mentally healthy learners. The article proposes a framework for this integration, demonstrating that prioritizing wellbeing is not a distraction from academic goals but is, in fact, the essential foundation for achieving them. Ultimately, equipping students with the skills to navigate complexity and adversity is the most critical lesson they can learn.